2014
DOI: 10.1007/s00453-014-9904-6
|View full text |Cite
|
Sign up to set email alerts
|

On Feedback Vertex Set: New Measure and New Structures

Abstract: We present a new parameterized algorithm for the feedback vertex set problem (fvs) on undirected graphs. We approach the problem by considering a variation of it, the disjoint feedback vertex set problem (disjoint-fvs), which finds a feedback vertex set of size k that has no overlap with a given feedback vertex set F of the graph G. We develop an improved kernelization algorithm for disjointfvs and show that disjoint-fvs can be solved in polynomial time when all vertices in G \ F have degrees upper bounded by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 25 publications
1
58
0
Order By: Relevance
“…-Third, A constructs an auxiliary graph G = (V , E ) by setting V to be the set of equivalence classes of ∼ and E to contain an edge between A, B ∈ V iff there exist vertices a ∈ A, b ∈ B such that ab ∈ E(G). -Finally, A tries to find a feedback vertex set in G of size at most j in time O(3.83 j · j|V | 2 ) [7]. If no such feedback vertex set exists, then A terminates the given branch; otherwise it adds the feedback vertex set to S and outputs S.…”
Section: Lemma 11 It Is Possible To Compute a K-well-structured Modulmentioning
confidence: 99%
“…-Third, A constructs an auxiliary graph G = (V , E ) by setting V to be the set of equivalence classes of ∼ and E to contain an edge between A, B ∈ V iff there exist vertices a ∈ A, b ∈ B such that ab ∈ E(G). -Finally, A tries to find a feedback vertex set in G of size at most j in time O(3.83 j · j|V | 2 ) [7]. If no such feedback vertex set exists, then A terminates the given branch; otherwise it adds the feedback vertex set to S and outputs S.…”
Section: Lemma 11 It Is Possible To Compute a K-well-structured Modulmentioning
confidence: 99%
“…Given a graph G and an integer k as input, the Feedback Vertex Set problem asks whether G has a vertex subset of size at most k whose removal makes it a forest, which is a graph without cycles. The Feedback Vertex Set problem is known to admit an FPT algorithm [2,12] and the running time has been subsequently improved by a series of papers [24,17,15,11,5,3,8,20]. Also, Thomassé [27] showed that it admits a kernel on Opk 2 q vertices.…”
Section: Introductionmentioning
confidence: 99%
“…Now that we have stored the entire graph, use any one of the various known FPT algorithms [8,23] to solve the F V S(k) problem.…”
mentioning
confidence: 99%